2018
DOI: 10.18517/ijaseit.8.2.4348
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Study of Application of Lead Rubber Bearings in Kutai Kartanegara Steel Arch Bridge

Abstract: The basic concept of the application of base isolation is by extending the natural period of the structure in order to provide lower seismic acceleration. The paper focuses on the investigation of the application of lead-rubber bearings (LRBs) instead of pot bearings in a new Kutai Kartanegara steel arch bridge located in East Kalimantan province. Even though the bridge is known located in Seismic Zone 1 (the zone with the least seismic risk as per SNI 2833-2013), the study was extended for other higher risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…A numerical study by Edalathi and Tahghighi [8] showed that the application of LRB instead of ERB increased the structural flexibility, significantly reduced the base shear, bending moment, deck acceleration, pier displacement, and earthquake input energy of a continuous box girder bridge. Another study also showed that LRB significantly reduced the base shear of the suspension bridge [9] and the pier displacement of the continuous box girder bridge [10].…”
Section: Introductionmentioning
confidence: 90%
“…A numerical study by Edalathi and Tahghighi [8] showed that the application of LRB instead of ERB increased the structural flexibility, significantly reduced the base shear, bending moment, deck acceleration, pier displacement, and earthquake input energy of a continuous box girder bridge. Another study also showed that LRB significantly reduced the base shear of the suspension bridge [9] and the pier displacement of the continuous box girder bridge [10].…”
Section: Introductionmentioning
confidence: 90%
“…Lately, this technology is used not only for structures of high importance but also for residential and low-rise buildings. The efficiency of base isolator depends on the amount of energy dissipated by the isolator, the flexibility of superstructure, efficiency of base isolator [6], and the ratio of base isolation mass to superstructure mass. The effect on the efficiency of base isolation and dissipation of hysteretic energy has an indirect relation with the post to pre-yield stiffness of base isolator [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vasant et al [35] had studied the difference between a bi-linear model and an equivalent linear elastic-viscous damping model of the base isolation. The parameters of hysteresis loops in the bilinear model of base isolation have a significant influence on the response of base-isolated structure which did not portray the equivalent linear model of base isolation [35]. Azawi et al [36] had modeled the base isolation as a two spring and a deep beam where the energy dissipation of their model been assumed as equivalent viscous damping.…”
mentioning
confidence: 99%